On the validity of longitudinal comparisons of central location consumer testing results prior to COVID‐19 versus home use testing data during the pandemic. Issue 10 (17th September 2021) - Shi, Menghan; Stelick, Alina; Licker, Susan; Dando, Robin
Abstract : Abstract: Consumer testing assays a panel's liking of a food or other sensory stimulus. However, liking can be influenced by mood, with people feeling more uncomfortable, or more unhappy reporting lower liking ratings than those in a higher affect. Though consumer testing typically takes place as a central location test (CLT, usually in a set of standardized sensory booths), the COVID‐19 pandemic has resulted in a global pivot to home use tests (HUTs), where panelists can taste and smell samples unmasked more safely while in their own homes. Unfortunately, as this situation differs in many ways to a central location test, this puts the validity of longitudinal comparisons of liking scores under question. Further, as people across the globe report feelings of worry, unease, and stress during the pandemic, this may present a second source of variation in affect with previous years. We tested a set of snack bar samples both at home and in a central location, in repeated measures with the same panel, to test the validity of comparisons across locations. We further compared CLT results to those when testing the same samples in a previous year. Finally, we performed a meta‐analysis of existing data on this subject. While liking behavior in CLTs did not differ between years, panelists rated some samples higher when in their own homes, in line with results from the meta‐analysis of previous reports. Interestingly, panelists in the study also assigned fewer penalties in the HUT, implying a less analytical mindset when in the home. Results suggest that care should be taken when comparing results taken at home during the COVID‐19 pandemic to those taken previously in a central location. Practical Application: Consumer testing is applied in the food industry to evaluate a panelist's liking for a food product or stimulus. However, liking is also dependent on factors extrinsic to the samples tested. Thus, with the switch to in‐home testing due to COVID‐19, we compared liking scores from in‐home and central locations testing, with higher scores common in HUTs.